2021
DOI: 10.2147/rru.s312566
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Prostatic Carcinoma – A Clinical Case and Literature Review

Abstract: Cystic formations in the prostate are quite common, but the vast majority are benign. The cystic form of prostate adenocarcinoma can present unexpected symptoms, and management can be difficult because of the local advanced stage of the disease. A unique feature of this case is the surgical local cancer treatment. In this clinical case, we describe the literature surrounding this rare form of neoplasm. We present a clinical case of a rare form of prostate cancer in a 71-year-old male who was admitted to ER wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some of them were due to intra-tumor necrosis or hemorrhage. Previously, Popov et al reported a case 45mm cystic PCa was diagnosed by percutaneous puncture and hormone therapy was followed by radical prostatectomy 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were due to intra-tumor necrosis or hemorrhage. Previously, Popov et al reported a case 45mm cystic PCa was diagnosed by percutaneous puncture and hormone therapy was followed by radical prostatectomy 5 ) .…”
Section: Discussionmentioning
confidence: 99%